Special Support for Behavior Difficulties and Engagement in Swedish Preschools - Almqvist, Lena; Sjöman, Madeleine; Golsäter, Marie; Granlund, Mats (Frontiers in Education, 2018)
The Swedish preschool curriculum stipulates that all children independent of support needs should attend mainstream preschool groups, with equal opportunities for learning and engagement. Preschool teachers are responsible for paying attention to children in need of special support to achieve this. How support is provided for children in need of special support due to behavior difficulties in Swedish preschools varies, however. Some children, often formally identified as in need of special support, are supported by preschool staff supervised by external services. Other children receive support initiated and implemented by preschool staff, without supervision from external services. A further number of children receive no support for behavior difficulties, on top of what is provided to all children. This study investigated associations between support format (i.e. supervised support, staff-initiated support or no additional support), support content (i.e. implementation of support), behavior difficulties, socio-demographics and engagement. A mixed methods approach was used with a sample of 232 preschool children 15 to 71 months with assessed behavior difficulties. Preschool staff reported on the children’s engagement, behavior difficulties, socio-demographics and support provision. Logistic regression models were used to analyze the probability of children receiving either support format. Content analysis was used to categorize the support content, reported by preschool staff through open-ended questions. Point-biserial correlations were used to test associations between support content, behavior, socio-demographics and engagement. All children receiving supervised support for behavior difficulties were formally identified by external services as in need of special support. Supervised support was also more common if children disturbed the free play in the preschool group, with the most frequent support being collaboration with external teams. Staff-initiated support was most commonly given to children with high engagement, and for children who are not early second language learners. These children were most frequently supported by staff paying attention to negative behavior. Children who were not perceived as a burden to the group were less likely to receive any form of additional support. Ways of managing the preschool group seem to guide support strategies for children with behavior difficulties, rather than child-focused strategies emphasizing engagement in everyday activities.